STUDENT ACTUALIZATION IN IMPROVING LEARNING OUTCOMES TOWARDS A HIGH-PERFORMING SCHOOL - Habibi Muhammad, Devy; Khosiah, Nur; Adawiyah , Robiatul (International Journal of Multidisciplinary Reseach, 2025)
This Community Service (PKM) activity aims to improve students' self-actualization skills in support of improving learning outcomes towards achieving high-achieving schools at MA Nurul Islam Probolinggo. The main problems faced are low motivation, self-confidence, and students' independent learning abilities. The activity was implemented using a technical assistance approach through training and workshops that emphasize participatory and reflective learning. The activity participants numbered 24 students who were selected purposively based on their level of motivation and learning participation. The results of the activity showed a significant increase in aspects of learning motivation, critical thinking skills, and skills in planning learning strategies. Students began to demonstrate independence and creativity in the learning process, as well as the courage to express opinions in class. This activity also had a positive impact on teachers and the school environment through increased interaction and collaboration in learning. The technical assistance approach has proven effective in developing self-actualization and building competitive student character. This program is expected to become a model of sustainable mentoring for madrasas in creating a creative, religious, and high-achieving learning environment.